Parents' Satisfaction On The Quality Of Dental Care Provided By Dental Students At IIUM Paediatric Dental Clinic - Ali Yeon, Asilah Anis Bt; Kamaruddin, Athirah Izyan bt; Harun, Nor Asilah bt; Kusumawardani, Anisa (IIUM Medical Journal Malaysia, 2017)
Introduction: In dental schools, the clinical students are closely supervised to ensure a good quality of care delivery. However, little is known about the relation between the patients' satisfaction and the quality of care they received, therefore the aim of this study was to assess the relation between parents' satisfaction and the quality of dental care provided by dental students at IIUM students' polyclinic during paediatric clinical session. Materials and Methods: A self-administered questionnaire on service quality, interpersonal communication, and efficacy and treatment outcome dimensions were distributed to parents who attended their children dental treatment from September 2016 until December 2016. Meanwhile, the students' performances were assessed for their clinical and soft skills by the allocated paediatric dentistry lecturer. Data collected were analysed by using X² test. Results: 42 questionnaires and assessment forms were completed and analysed. The result showed 71.1% of the parents were satisfied with the quality of dental care provided despite the students' performance outcomes were moderate (84.2%). There is no significant difference between parents' satisfaction and the quality of dental care provided by the dental students (p>0.05). Mother showed higher percentage of satisfaction (60%) compared to father (36.4%). However, there is no significant relation between parents' satisfaction and the gender of the parents (p=0.076). Conclusion(s): Generally, parents are satisfied with the dental care provided by the dental students at IIUM Paediatric Dental Clinic regardless of the quality. Hence, parents' satisfaction could not be the best tool to assess the quality of care provided by the operators.